Penguatan Moderasi Beragama dan Pelajar Pancasila pada Kelembagaan Pendidikan Islam di Pondok Pesantren Al-Munir Lebak Banten - Wasehudin, Wasehudin; Upiyani, Upiyani (STAI Auliaurrasyidin Tembilahan, 2024)
Pondok Pesantren, as religious education institutions, play an important role in promoting a moderate understanding of religion in Indonesia. Despite widespread support for religious moderation by various stakeholders, there is growing concern about the religious practices of the population. This is evidenced by the presence of extremist movements and acts of terrorism in Indonesia, such as the terrorist attack on the Cathedral Church in Makassar on March 28, 2021. The attack was carried out by the Jamaah Ansharut Daula network, commonly known as JAD. The research will utilize a qualitative approach, using a phenomenological study design. The researcher examines the data, converting interview recordings into written text through transcription. The results of existing data will then be subject to qualitative descriptive analysis. The results show, steps that can be taken in strengthening religious moderation and the profile of Pancasila by maintaining religious diversity, strengthening inter-religious relations, offering a thorough religious education that is reasonable and balanced, promoting tolerance, engaging in efforts to increase tolerance, and promoting unity between religions.